Photoionization of the aqueous phase: clusters, droplets and liquid jets. Issue 22 (5th May 2022) - Signorell, Ruth; Winter, Bernd
Abstract : This perspective article reviews specific challenges associated with photoemission spectroscopy of bulk liquid water, aqueous solutions, water droplets and water clusters. Abstract : This perspective article reviews specific challenges associated with photoemission spectroscopy of bulk liquid water, aqueous solutions, water droplets and water clusters. The main focus lies on retrieving accurate energetics and photoelectron angular information from measured photoemission spectra, and on the question how these quantities differ in different aqueous environments. Measured photoelectron band shapes, vertical binding energies (ionization energies), and photoelectron angular distributions are influenced by various phenomena. We discuss the influences of multiple energy-dependent electron scattering in aqueous environments, and we discuss different energy referencing methods, including the application of a bias voltage to access absolute energetics of solvent and solute. Recommendations how to account for or minimize the influence of electron scattering are provided. The example of the hydrated electron in different aqueous environments illustrates how one can account for electron scattering, while reliable methods addressing parasitic potentials and proper energy referencing are demonstrated for ionization from the outermost valence orbital of neat liquid water.